Effect of Enamel Caries Lesion Baseline Severity on Fluoride Dose-Response. (27th March 2017) - Lippert, Frank
Abstract : This study aimed to investigate the effect of enamel caries lesion baseline severity on fluoride dose-response under pH cycling conditions. Early caries lesions were created in human enamel specimens at four different severities (8, 16, 24, and 36 h). Lesions were allocated to treatment groups (0, 83, and 367 ppm fluoride as sodium fluoride) based on Vickers surface microhardness (VHN) and pH cycled for 5 d. The cycling model comprised 3 × 1 min fluoride treatments sandwiched between 2 × 60 min demineralization challenges with specimens stored in artificial saliva in between. VHN was measured again and changes versus lesion baseline were calculated (ΔVHN). Data were analyzed using two-way ANOVA (p < 0.05 ). Increased demineralization times led to increased surface softening. The lesion severity×fluoride concentration interaction was significant (p < 0.001 ). Fluoride dose-response was observed in all groups. Lesions initially demineralized for 16 and 8 h showed similar overall rehardening (ΔVHN) and more than 24 and 36 h lesions, which were similar. The 8 h lesions showed the greatest fluoride response differential (367 versus 0 ppm F) which diminished with increasing lesion baseline severity. The extent of rehardening as a result of the 0 ppm F treatment increased with increasing lesion baseline severity, whereas it decreased for the fluoride treatments. In conclusion, lesion baseline severity impacts the extent of the fluoride dose-response.